The effects of three different background music on verbal and spatial task performance in learning - Abdul Jalil, Amalina Ulya; Buang, Norazirah; Naseri, Sousan; Ma'rof, Aini Marina (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
The objective of this preliminary experimental study is to investigate the effects of three different backgrounds of music: instrumental, vocal and silence on verbal and spatial task performance in learning. The study samples were from postgraduate students of a public research university in Malaysia which consisted of 36 students. Data was analyzed using IBM Statistics in which independent sample t-tests and two-way analysis variance (ANOVA) were conducted. The t-tests show that there are significance differences between instrumental condition (t = 2.06, p = 0.018), vocal condition (t = 1.101, p = 0.172) and silent condition (t = 2.712, p = 0.022) on the verbal and spatial task performance. Two-way ANOVA music within group Greenhouse-Geisser was reported in the significant level (p<0.05). The findings provide information that music – when listened to in an appropriate form – can actually help students to perform better in their learning.